2013
DOI: 10.1073/pnas.1306539110
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering archaeological landscapes at Angkor using lidar

Abstract: Previous archaeological mapping work on the successive medieval capitals of the Khmer Empire located at Angkor, in northwest Cambodia (∼9th to 15th centuries in the Common Era, C.E.), has identified it as the largest settlement complex of the preindustrial world, and yet crucial areas have remained unmapped, in particular the ceremonial centers and their surroundings, where dense forest obscures the traces of the civilization that typically remain in evidence in surface topography. Here we describe the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
209
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(226 citation statements)
references
References 32 publications
(62 reference statements)
1
209
0
2
Order By: Relevance
“…However the application of the technique gained significant momentum for prospection in regions covered with dense vegetation, including the multi-layer tropical and sub-tropical rain forests of South and Central America [11,12], as well as South East Asia [13][14][15]. The ability to map landscapes hidden beneath dense vegetation is resulting in a revolution in archaeology arguably comparable to that caused by the introduction of radiocarbon dating some decades ago [13].…”
Section: Introductionmentioning
confidence: 99%
“…However the application of the technique gained significant momentum for prospection in regions covered with dense vegetation, including the multi-layer tropical and sub-tropical rain forests of South and Central America [11,12], as well as South East Asia [13][14][15]. The ability to map landscapes hidden beneath dense vegetation is resulting in a revolution in archaeology arguably comparable to that caused by the introduction of radiocarbon dating some decades ago [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is a powerful tool to analyse past settlement and landscape modification at a large scale. Use cases such as in [20][21][22][23] helped remove preconceptions about settlements size, scale, and complexity by providing a complete view of the topography and alterations to the environment, but while it provided new research and analysis directions, the LiDAR data did not leverage 3D point clouds considered too heavy and too raw to provide a source of information.…”
Section: Archaeological Field Workmentioning
confidence: 99%
“…In addition to the shift in scale, the details of the patterns of occupation outside the dense cores of these cities are emerging through systematic study of the topographic models, combined with targeted survey work on the ground. Notable projects working on this topic include the Cambodia Archaeological Lidar Initiative ( http://angkorlidar.org/ ), whose study areas include Ankor Wat, Sambor Prei Kuk, Koh Ker, and Phnom Kulen (Evans et al 2013 ), studies of Caracol in Belize, led by Chase and Chase (Chase et al 2011), and work at Angamuco in Mexico by Fisher (Fisher and Leisz 2013 ). A discussion of the impacts of ALS on this area of study can be found in Chase et al ( 2012 ) wherein they note that lidar data, "are changing commonly held interpretations of societal development profoundly."…”
Section: Topography As Archaeological Information: Diffuse Urbanism Imentioning
confidence: 99%